Preparation and detection application of monoclonal antibodies against Potato virus Y - SONG Ge; GUO Yushuang; RAO Lixia; ZHOU Xueping; WU Jianxiang (浙江大学学报. 农业与生命科学版, 2016)
Potato virus Y (PVY) is one of the most important potato viruses causing serious economic loss in potato industry worldwide. Establishment of a sensitive and specific virus detection technique is the key to prevent and control PVY.To provide material and technical support for the diagnosis, scientific prevention and control of PVY in fields, four monoclonal antibodies (MAbs) against PVY were prepared with the hybridoma technique, and four serological assays were developed in this study.PVY particles with 730 nm × 11 nm were obtained from PVYN-infected tobacco plants with a high yield purification method, and which were used as the immunogen. Four hybridoma cell lines (3B2, 3E4, 20B2 and 25C2) secreting sensitive and specific MAbs against PVY were prepared. Titers of the four MAbs in ascetic fluids secreted by prepared hybridoma cells were ranged 10-6 to 10-7 by an indirect ELISA. Western blot analyses indicated that three MAbs (3E4, 3B2 and 20B2) could specifically react with 30 ku protein, which was supposed to be the coat protein of PVY based on the size of the protein. The MAb 25C2 could react with an approximately 55 ku protein, which was supposed to be HC-Pro based on the molecular mass of the protein. Based on the prepared MAbs, four serological assays, ACP-ELISA, dot-ELISA, tissue blot-ELISA and immunocapture-reverse transcription-polymerase chain reaction (IC-RT-PCR) were developed for detecting PVY in plants. Specificity analyses of the four developed serological assays demonstrated that all assays could accurately detect virus in PVY-infected plant tissues, and have negative detection results with the leaf tissue crude extracts from PVS, PVA, PVX, PLRV-infected plant tissues or healthy potato and tobacco plant tissues. The sensitivity analyses indicated that the developed ACP-ELISA, dot-ELISA could specifically detect virus in PVY-infected plant tissue crude extracts diluted at 1∶81 920 and 1∶10 240 (g/mL), respectively. The developed IC-RT-PCR was the most sensitive, and could successfully detect virus in PVY-infected plant tissue crude extracts diluted at 1∶5 242 880 (g/mL). Thirty potato field samples from Yunnan Province were detected for the presence of PVY by the developed serological assays. The detection results of serological assays were the same as the result of RT-PCR, and 20 of the 30 potato field samples were PVY-positive. Sequencing and sequence comparative analysis of PCR products proved that the positive samples detected by the serological assays were really infected by PVY.The anti-PVY MAbs and the developed serological detection assays will provide material and technology for detecting and quarantining PVY, breeding virus-free seed potatoes and establishing scientific prevention and control system of the disease.